Self-control and multitasking digital media: Study of K-Pop fans in Makassar - Sinar; Thalib, Tarmizi; Gismin, Sitti Syawaliyah (Digital Theory, Culture & Society, 2024)
This study investigates the relationship between self-control and media multitasking among K-Pop fans in Makassar. The research involved 467 participants aged 18–25 years, employing the Media Use Questionnaire (MUQ) to assess multitasking behaviors and a self-control scale based on Tangney's theoretical framework. Data analysis using Pearson Product Moment correlation revealed a weak yet significant positive relationship (r = 0.124, p < 0.05), indicating that higher self-control correlates with increased multitasking. This phenomenon reflects the integration of digital media into daily routines, where media multitasking becomes a habitual activity influenced by technological advancements and social contexts. Findings highlight that self-control plays a role in managing digital consumption, aligning with prior studies linking low self-control to problematic media usage. The study underscores the implications of multitasking behaviors on cognitive and emotional well-being, emphasizing the need for strategies to foster balanced digital media engagement. These results contribute to understanding digital media habits within the context of K-Pop fandom, offering insights for psychological and cultural studies on media behavior.